Perjuangan dan Kemajuan Islam di Seluruh Dunia: Dari Rasulullah Hingga Khulafa' Rasyidin - Ratu Amalia Hayani; Iwan Ridwan; Taufik Setyaudin (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2025)
This study discusses the struggle and progress of Islam from the time of the Prophet Muhammad to the period of the Rightly-Guided Caliphs, which was a crucial phase in the history of Islam. This study analyses various aspects of Islamic development, including the laying of religious foundations, the formation of early Islamic society, and the expansion of territory, using a literature review. The main focus is on the efforts of the Prophet in uniting the Arab tribes and building a socio-political system based on Islamic values, as well as the success of the Rightly Guided Caliphs in expanding the territory of Islam. This study also highlights significant developments in the aspects of government, science, and the application of Islamic values such as justice, deliberation, and tolerance. The results of the study show that this period became a strong foundation for the development of Islamic civilisation in the following period, with a continuing impact to this day.